Single Center Experience of Fluoroless AVNRT Ablation Guided by Electroanatomic Reconstruction in Children and Adolescents. Issue 12 (28th May 2013) - SCAGLIONE, MARCO; EBRILLE, ELISA; CAPONI, DOMENICO; BLANDINO, ALESSANDRO; DI, PAOLO; SIBOLDI, ALESSANDRA; BERTERO, GIOVANNI; ANSELMINO, MATTEO; RAIMONDO, CRISTINA; SARDI, DAVIDE; GABBARINI, FULVIO; MARASINI, MAURIZIO; et al.
<x xml:space="preserve">Abstract</x> Background Anatomical considerations and risks related to x‐ray exposure make atrioventricular nodal reentrant tachycardia (AVNRT) ablation in pediatric patients a concerning procedure. We aimed to evaluate the feasibility, safety, and efficacy of performing fluoroless slow‐pathway cryoablation guided by the electroanatomic (EA) mapping in children and adolescents. Methods Twenty‐one consecutive patients (mean age 13.5 ± 2.4 years) symptomatic for AVNRT were prospectively enrolled to right atrium EA mapping and electrophysiological study prior to cryoablation. Cryoablation was guided by slow‐pathway potential and performed using a 4‐mm‐tip catheter. Results Sustained slow‐fast AVNRT was inducible in all the patients with a dual AV nodal physiology in 95%. Acute success was achieved in 100% of the patients with a median of two cryo‐applications. Fluoroless ablation was feasible in 19 patients, while in two subjects 50 seconds and 45 seconds of x‐ray were needed due to difficult progression of the catheters along the venous system. After a mean follow‐up of 25 months, AVNRT recurred in five patients. All the recurrences were successfully treated with a second procedure. In three patients, a fluoroless cryoablation with a 6‐mm‐tip catheter was successfully performed, while in the remaining two patients, a single pulse of 60 seconds of radiofrequency energy was applied under fluoroscopic monitoring. No complications occurred. Conclusions Combination of EA mapping systems and cryoablation may allow to perform fluoroless slow‐pathway ablation for AVNRT in children and adolescents in the majority of patients. Fluoroless slow‐pathway cryoablation showed a high efficacy and safety comparable to conventional fluoroscopy guided procedures.